Benefits of modest weight or waist circumference loss in a remote North Queensland Indigenous population - Katina D'Onise; Robyn A. McDermott; Sandra K. Campbell (Elsevier, 2013)
Abstract Objective : To quantify the potential benefit to individuals of differing magnitudes of weight or waist circumference loss in an Indigenous population. Method : Data were from the Well Person's Health Check, a cohort study in 19 rural Indigenous communities in Far North Queensland. Baseline data were collected between 1998 and 2000 from 2,583 people aged 15 to 75, an estimated participation rate of 44.5%. Follow‐up data were collected between 2004 and 2007 from 729 participants. Associations between change in weight and waist circumference for those who were overweight or obese (n=486) with changes in serum lipids, fasting glucose, blood pressure and Gamma‐Glutamyltransferase (GGT) were estimated using linear regression. Results : Weight or waist circumference loss was associated in a dose response fashion with blood pressure reduction (e.g. 10% or greater weight loss compared with no weight loss was associated with reduction of 11.3 mmHg systolic (95% confidence interval −17.8, −4.8). Those with greater waist circumference loss had a greater reduction in GGT (−8.3, 95% confidence interval −23.5, 6.8) but there was no apparent increase in GGT reduction with increasing weight loss, although these were measured with low precision. There was no apparent effect of either weight or waist circumference loss on serum lipids and fasting glucose in this population. Conclusions : This study shows potentially large beneficial effects of weight or waist circumference loss over several years in a remote living Indigenous cohort. The associations were large enough to be of clinical benefit, despite weight loss being modest for most.